SISTEM PEMERINTAHAN PADA MASA DEMOKRASI LIBERAL TAHUN 1949-1959 - Hakiki, Paizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Starting fromthe recognition ofsovereignty, Indonesia entered a periodof liberal democracy. Liberal democracy periodappliesbetween the years1949-1959.characterized bythe flourishing ofpolitical partiesan denactment of parliamentary cabinet.Liberal democracyin Indonesia is characteri zedby politicalt urmoilandpoliticalachievements.Political achievementssuchastheimplementation of a multiparty system anddemocraticelections.Political turmoilinthe form ofsuccessivecabinetandprolongeddebateinkontituante.Used to describealiberaldemocracyandademocraticpoliticalsystem.TheConstitutioncanbeusedrepublicoraconstitutionalmonarchy.Liberaldemocracyusedbycountriesthatfollowthepresidentialsystem,parliamentarysystemor asemi-presidential system. Therefore, researchersinterestedinconductingresearchentitled:SystemofGovernmentinLiberalDemocracyyearperiodfrom 1949 to 1959. This studyaims todetermineIndonesian systemof democracyduringthe Liberalyears1949-1959.Thisresearchmethodis the methodthat isthe history ofa set of principlesorrulesthatprovideeffectiveassistancein an effort tocollect dataormaterialsforhistory,criticallyassess, andthen presentsasynthesis ofthe resultsin written form(NugrohoNoto Susanto, 1984:11) .System of government in the political field during the Parliamentary democracy, oralso known as Liberal democracyis aparliamentarycabinet system.This rulespecifiesthatthesystemcabinetsorministersareresponsibleto parliament. Parliamentary cabinet systemalsointroduced a system of voting (voting) isusedin thegeneral election(election), motion(do not believe),and the demonstrationas a formof expressing the people'sright to participate in politics.Keyword: Liberal Democracy Year 1949-1959